Correlation between increased orbital volume and enophthalmos and diplopia in patients with fractures of the orbital floor or the medial orbital wall. Issue 9 (September 2018) - Schönegg, Daphne; Wagner, Maximilian; Schumann, Paul; Essig, Harald; Seifert, Burkhardt; Rücker, Martin; Gander, Thomas
Abstract: Fractures of the orbital floor and medial orbital wall (blowout fractures) are common midface injuries. Diagnostic methods and treatment options have improved over recent years, due to threedimensional image processing and the use of patient-specific implants. Nonetheless, the indications for orbital reconstructive surgery are still controversial. Previous authors have reported a linear correlation between post-traumatic increases in orbital volume and enophthalmos and diplopia. Post-traumatic increases in orbital volume are often considered to be predictive of long-term symptoms; therefore, it is commonly recommended that orbital volume increases be treated as an indication for early reconstructive surgery. However, the results of this study did not show any statistically significant long-term linear correlation between increased orbital volume and enophthalmos or diplopia, and the performance of orbital volume as a predictor of ocular symptoms was poor. Hence, we do not consider increased post-traumatic orbital volume to be particularly useful for predicting late enophthalmos or diplopia. However, a statistical correlation between fractures of the anterior and medial thirds of the orbital floor and double vision was found. As such, fractures of the middle and anterior third should be regarded as problematic, and surgical reconstruction should be considered in these cases.